Protein Kinase C Inhibition Mediates Neuroblast Enrichment in Mechanical Brain Injuries - García-Bernal, Francisco; Geribaldi-Doldán, Noelia; Domínguez-García, Samuel; Carrasco, Manuel; Murillo-Carretero, Maribel; Delgado-Ariza, Antonio; Díez-Salguero, Mónica; Verástegui, Cristina; Castro, Carmen (Frontiers in Cellular Neuroscience, 2018)
Brain injuries of different etiologies lead to irreversible neuronal loss and persisting neuronal deficits. New therapeutic strategies are emerging to compensate neuronal damage upon brain injury. Some of these strategies focus on enhancing endogenous generation of neurons from neural stem cells to substitute the dying neurons. However, the capacity of the injured brain to produce new neurons is limited, especially in cases of extensive injury. This reduced neurogenesis is a consequence of the effect of signaling molecules released in response to inflammation, which act on intracellular pathways, favoring gliogenesis and preventing recruitment of neuroblasts from neurogenic regions. Protein kinase C (PKC) is a family of intracellular kinases involved in several of these gliogenic signaling pathways. The aim of this study was to analyze the role of PKC isozymes in the generation of neurons from neural progenitor cells in vitro and in vivo in brain injuries. PKC inhibition in vitro, in cultures of neural progenitor cells (NPC) isolated from the subventricular zone of postnatal mice, leads differentiation towards a neuronal fate. This effect is not mediated by classical or atypical PKC. On the contrary, this effect is mediated by novel PKCε, which is abundantly expressed in NPC cultures under differentiation conditions. PKCε inhibition by siRNA promotes neuronal differentiation and reduces glial cell differentiation. On the contrary, inhibition of PKCθ exerts a small anti-gliogenic effect and reverts the effect of PKC inhibition on neuronal differentiation when both siRNAs are used in combination. Interestingly, in cortical brain injuries we have found expression of almost all PKC isozymes found in vitro. Inhibition of PKC activity in this type of injuries leads to neuronal production. In conclusion, these findings show an effect of PKCε in the generation of neurons from NPC in vitro, and they highlight the role of PKC isozymes as targets to produce neurons in brain lesions.